A Brief Overview of the STP 35th Annual Symposium on the Basis and Relevance of Variation in Toxicologic Responses. (January 2017) - Irizarry, Armando R.; Gropp, Kathryn E.; Dixon, Darlene
The title of the 2016 Society of Toxicologic Pathology (STP) Symposium was the "Basis and Relevance of Variation in Toxicologic Responses." Many factors may contribute to variation in toxicologic responses and can confound results, complicate interpretation of data, interfere with reproducibility, and make extrapolation to humans problematic. This brief overview summarizes speaker presentations from each session which describes important factors that may impact the interpretation of nonclinical discovery and developmental toxicity studies. In addition, summaries of the Continuing Education (CE) courses and other educational events that occurred during the Symposium are highlighted.